2017
DOI: 10.1016/j.virol.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Latent Membrane Protein 2A (LMP2A) enhances IL-10 production through the activation of Bruton's tyrosine kinase and STAT3

Abstract: Previous data demonstrate that Epstein-Barr Virus Latent Membrane Protein 2A (LMP2A) enhances IL-10 to promote the survival of LMP2A-expressing B cell lymphomas. Since STAT3 is an important regulator of IL-10 production, we hypothesized that LMP2A activates a signal transduction cascade that increases STAT3 phosphorylation to enhance IL-10. Using LMP2A-negative and –positive B cell lines, the data indicate that LMP2A requires the early signaling molecules of the Syk/RAS/PI3K pathway to increase IL-10. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…In combination with the findings reported here, these data suggest the importance of this chemokine in the life cycle of EBV and the development of HL tumor microenvironment. Furthermore, we and others demonstrated that both LMP1 and LMP2A result in the increase of the prosurvival cytokine, IL‐10 . Once again, the two proteins use distinct mechanisms to increase IL‐10: LMP1 uses p38K in addition to PI3K to increase IL‐10, while LMP2A uses the activation of the PI3K/BTK/STAT3 pathway without the need for p38K activation and data presented here).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In combination with the findings reported here, these data suggest the importance of this chemokine in the life cycle of EBV and the development of HL tumor microenvironment. Furthermore, we and others demonstrated that both LMP1 and LMP2A result in the increase of the prosurvival cytokine, IL‐10 . Once again, the two proteins use distinct mechanisms to increase IL‐10: LMP1 uses p38K in addition to PI3K to increase IL‐10, while LMP2A uses the activation of the PI3K/BTK/STAT3 pathway without the need for p38K activation and data presented here).…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, we and others demonstrated that both LMP1 and LMP2A result in the increase of the prosurvival cytokine, IL-10. 24,25,55 Once again, the two proteins use distinct mechanisms to increase IL-10: LMP1 uses p38K in addition to PI3K to increase IL-10, 55 while LMP2A uses the activation of the PI3K/BTK/STAT3 pathway without the need for p38K activation 25 and data presented here). Future studies need to address whether the activation of NF-κB is additive when both LMP1 and LMP2A are present, since previous studies indicate that these two proteins can positively affect the signaling of one another.…”
Section: Lmp2a-mediated Nuclear Localization Of Nf-κbmentioning
confidence: 68%
See 2 more Smart Citations
“…LMP2A + Btk −/− mice exhibit an aggravated Xid phenotype compared with that of Btk −/− littermates, including immature phenotypes and decreased B cell numbers during B cell development, whereas the capability of LMP2A is partially restored in the absence of both Btk and RAG‐1, supporting the production of CD19 + IgM − B cells in the bone marrow . Another study demonstrated that LMP2A enhanced STAT3‐mediated IL‐10 production to promote the survival of EBV‐positive B cell lymphomas through the activation of Btk . These findings highlight that Btk is a potential drug target for the treatment of EBV‐associated LMP2A‐expressing B cell lymphomas.…”
Section: Btk and Pathogenic Microorganism Infectionsmentioning
confidence: 97%